STRATEGI PARTNERSHIP DALAM UPAYA MEMBANGUN BRAND VALUECITILINK{STUDI KASUS : PROGRAM BOARDING PASS TRUE VALUE (BPTV)} - Putri, Nabhila Risvan; Simandjuntak, Lintong; Priyanto, Priyanto (Journal of Indonesian Tourism and Policy Studies, 2017)
The purpose of this Project is to discuss (I) about the program of BPTV (II) explain the procedure of cooperation with merchant (III) and explain the obstacles faced by Citilink in BPTV program and its solution. The author also states which cities are available Citilink merchants, do not forget also the authors include the data of visitors who use the program BPTV. This program is a program of the Marketing Communication division, a sub-division of New Distribution Channel And Partnership (NDC). The method used in the manufacture and writing of this Final Project Task is a descriptive method through the written or oral words of the people and the behavior observed. The author also uses the method of observation is through field work practices conducted by the author at PT Citilink Indonesia for 3 months.